Genome-wide identification of NF-Y gene family in maize (Zea mays L.) and the positive role of ZmNF-YC12 in drought resistance and recovery ability - Cao, Liru; Ma, Chenchen; Ye, Feiyu; Pang, Yunyun; Wang, Guorui; Fahim, Abbas Muhammad; Lu, Xiaomin (Frontiers in Plant Science, 2023)
Nuclear factor Y (NF-Y) genes play important roles in many biological processes, such as leaf growth, nitrogen nutrition, and resistance. However, the biological functions of these transcription factor family members have not been systematically analyzed in maize. In the present study, a total of 52 ZmNF-Y genes were identified and classified into three groups in the maize genome.An analysis of the evolutionary relationship, gene structure, and conserved motifs of these genes supports the evolutionary conservation of NF-Y family genes in maize. The tissue expression profiles based on RNA-seq data showed that all genes apart from ZmNF-Y16, ZmNF-YC15, and ZmNF-YC17 were expressed in different maize tissues. A weighted correlation network analysis was conducted and a gene co expression network method used to analyze the transcriptome sequencing results, and six core genes responding to drought and rewatering were identified. A real time fluorescence quantitative analysis showed that these six genes responded to high temperature, drought, high salt, and abscisic acid (ABA) treatments,and subsequent restoration to normal levels. ZmNF-YC12 was highly induced by drought and rewatering treatments. The ZmNF-YC12 protein was localized in the nucleus, and the Gal4-LexA/UAS system and a transactivation analysis demonstrated that ZmNF-YC12 in maize (Zea mays) is a transcriptional activator that regulates drought resistance and recovery ability. Silencing ZmNF-YC12 reduced net photosynthesis, the chlorophyll content, antioxidant (superoxide dismutase, catalase, peroxidase and ascorbate peroxidase) system activation, soluble protein and proline contents, and increased the malondialdehyde content, the relative water content, and the water loss rate, which weakened drought resistance and the recovery ability of maize. These results provide insights into understanding the evolution of ZmNF-Y family genes in maize and their potential roles in genetic improvement. Our work provides a foundation for subsequent functional studies of the NF-Y gene family and provides deep insights into the role of the ZmNF-YC12 regulatory network in controlling drought resistance and the recovery ability of maize.